CRISPR/Cas9 disruption of EpCAM Exon 2 results in cell-surface expression of a truncated protein targeted by an EpCAM specific T cell engager - Andisheh Bagheri; Patricia A. Culp; Robert B. DuBridge; Tseng-hui Timothy Chen (Biochemistry and Biophysics Reports, 2022)
CRISPR/Cas9 gene-editing technology allows researchers to study protein function by specifically introducing double-stranded breaks in the gene of interest then analyze its subsequent loss in sensitive biological assays. To help characterize one of a series of highly potent, conditionally active, T cell engaging bispecific molecules called COBRA™, the human EpCAM gene was disrupted in HT29 cells using CRISPR/Cas9 and guide RNA targeting its Exon 2. Although a commercially available antibody indicated loss of cell-surface expression, the EpCAM targeting bispecific COBRA was still able to lyse these cells in a T cell dependent cellular cytotoxicity assay. RT-PCR sequence analysis of these cells showed a major alternative transcript generated after CRISPR/Cas9, with Exon 1 and 3 spliced together in-frame, skipping Exon 2 completely, to express a truncated cell-surface receptor recognized by the EpCAM-COBRA. Researchers who use CRISPR/Cas9 must be cognizant of this potential to express alternative versions of their proteins and use sensitive orthogonal detection methods to ensure complete gene disruption.